1999
DOI: 10.1007/s004300050099
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor necrosis factor (TNF)-? in the antitumor effect of intrapleural injection of Lactobacillus casei strain Shirota in mice

Abstract: The involvement of several cytokines in the antitumor effect induced by intrapleural (i.pl.) injection of heat-killed cells of Lactobacillus casei strain Shirota (LC 9018) in mice was investigated. Injection of LC 9018 i.pl. into Meth A fibrosarcoma (Meth A)-bearing mice not only significantly prolonged the survival of the mice, but also effectively inhibited the accumulation of malignant pleural fluid in the thoracic cavity. In the thoracic cavity of tumor-bearing mice treated with LC 9018, we observed large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Nonetheless, such an ability of LAB should not be considered detrimental. In fact, even though cytokines belonging to the TNF-␣ superfamily are connected to the occurrence of inflammatory diseases (54), they have also been shown to participate in the rejection of tumors and infections (55)(56)(57). Furthermore, the induction of TNF-␣ could be important for the initiation of cross talk among immune cells without causing any inflammation or detrimental effects (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, such an ability of LAB should not be considered detrimental. In fact, even though cytokines belonging to the TNF-␣ superfamily are connected to the occurrence of inflammatory diseases (54), they have also been shown to participate in the rejection of tumors and infections (55)(56)(57). Furthermore, the induction of TNF-␣ could be important for the initiation of cross talk among immune cells without causing any inflammation or detrimental effects (30).…”
Section: Discussionmentioning
confidence: 99%
“…Triggering of increased TNF-α production by pili encoded by B. bifidum PRL2010 may be an interesting feature of this species as one of the first colonizers of the human gut (3). In fact, cytokines belonging to the TNF-α superfamily are not only linked to the occurrence of inflammatory diseases (45), but also play a role in the rejection of tumors and the response to infections (46,47). In addition, the induction of TNF-α may be important for the initiation of cross-talk among immune cells without causing any inflammation or detrimental effects (43).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed that LAB exerts antitumor effects. Some LAB, such as Lactobacillus rhamnosus GG (Goldin et al, 1996), Lactobacillus acidophilus (Goldin and Gorbach, 1977;Lidbeck et al, 1992), Bifidobacterium longum (Reddy and Rivenson, 1993), Lactobacillus casei strain Shirota (Yasutake et al, 2000) and components of LAB (Shiomi et al, 1982) were shown to exert tumor-suppressing effects. For reduction of allergy, Matsuzaki et al (1998) reported that oral feeding of Lactobacillus casei strain Shirota effectively inhibited Immunoglobulin(Ig)E production both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%